Creative Problem Solving Learning to Fix Errors Eighth Grader In Problem Solving Matter - Irsyad, Yofa Muhammad; Suhito, Suhito; Suyitno, Amin (Department of Mathematics, Universitas Negeri Semarang, 2017)
Penelitian ini dilatarbelakangi oleh temuan kesalahan siswa dalam menyelesaikan soal pemecahan masalah. Tujuan penelitian ini adalah mendiagnosis tipe kesalahan siswa berdasarkan prosedur Newman, kesulitan belajar siswa, dan mengetahui keefektifan pembelajaran Creative Problem Solving untuk mengatasi kesalahan siswa. Subjek penelitian adalah 9 siswa kelas VIII D di SMP Negeri 18 Semarang, yaitu masing-masing 3 siswa dari kelompok atas, kelompok tengah, dan kelompok bawah. Pembelajaran dengan metode pemecahan masalah diajarkan kepada siswa untuk mengajarkan kemampuan pemecahan masalah. Hasil penelitian ini yaitu (1) tipe kesalahan yang dilakukan siswa kelas VIII D adalah comprehension errors (tipe C), transformation errors (tipe T), process skills errors (tipe P), dan encoding errors (tipe E); (2) letak kesulitan belajar paling banyak adalah menentukan nilai panjang, lebar, atau tinggi yang sesungguhnya dan sifat kesulitan belajar paling banyak adalah psikologis; dan (3) pembelajaran Creative Problem Solving efektif untuk mengatasi kesalahan siswa sebagai subjek penelitian berdasarkan prosedur Newman dalam menyelesaikan soal pemecahan masalah. This research was motivated by findings students’ mistakes in solving the problem-solving exercises. The purpose of this research is to diagnose students’ error type based on Newman’s procedure, students’ learning difficulties, and to know the effectiveness of Creative Problem Solving learning in solving students’ mistakes. The subjects of the research are taken from the 9 students of grade VIII D SMP Negeri 18 Semarang, respectively 3 students from the top group, middle group, and lower group. Learning process using problem-solving methods taught the students about the problem-solving skills. The results of this research are (1) the type of errors made by students in grade VIII D are comprehension errors (type C), transformation errors (type T), process skills errors (type P), dan encoding errors (type E); (2) the learning difficulties are mostly in determining the value of the length, width, or height of the real and the characteristics of learning difficulties are mostly in psychological; and (3) Creative Problem Solving learning effectively overcome the mistakes of research subjects based on Newman’s Procedure in solving the problem-solving exercises.